Preschool Teachers in Bottom-top Curriculum Change-Invigoration and Implementation - Reuben Sitonik Olkishoo; Francis Maina Gichuru; Christopher Khayeka-Wandabwa; Methody Florian Owaki; Stephen Wamalwa; Pamela A. Marinda; Tianxi Xu (ÜNİVERSİTEPARK Limited, 2019)
With Kenya having rolled out the Competence-Based Curriculum effective as from 2019, anchoring in it preschool education as an integral component, there is still a level of indistinctness as to the role of the preschool teacher in the core domains of curriculum development and reform. The perspective brings to light insights of preschool teacher engagement and interlinkage in effecting the much-desired curriculum development and reform through learner growth, creating an enabling environment, the need for preschool teacher involvement in curriculum evaluations, reforms and adaptability to transformation. The perspective examination integrates documentary analysis as well as discourse analysis. Evidently, progressive implementation of the Competence-Based Curriculum in preschool education alongside any desired adaptations in a timely, expertise and pragmatic manner driven by classroom realities is considered core in ensuring seamless successive transition of learners. It is not only the basis for foundational skills of literacy and numeracy, but also life skills grounding for learners. The findings examination posits for well-anchored and dynamic policy transition considerations at the governmental level on preschool teacher capacity development. As informed by the core domains of curriculum development, it is recommended that reform thought processes and ideologies ignited by preschool teachers from the grass-root levels should encourage a bottom-top channel of curriculum adjustment recommendations rather than a top-down, unilateral and bureaucratic system.